ONLINE BUSINESS OPERATIONAL STRATEGIES (GLORY ONLINE STORE CASE STUDY) - Rahmi Jamza; Noer Azam Achsani; Dikky Indrawan (School of Business, IPB University (SB-IPB), 2020)
The rapid development in the fashion industry due to the increasing use of technology shifts conventional methods of selling to online methods. Glory Online Store is one of the online stores that took the opportunity by selling fashion products for women via Instagram. To compete and gain more customers, Glory changed their operation strategy from drop shipper and reseller systems into an independent production. Hence, Glory requires the right operating strategy to maximize its business performance. This study aimed to: (1) identify the business processes on Glory’s Business internal environment, (2) identify the organizational structure on Glory’s Business internal environment, (3) formulate the Glory business operation strategy based on the results of the SWOT analysis evaluation and (4) redesign business processes on Glory’s Business internal environment. The research employed BPMN and SWOT analysis. In-depth interviews were used to collect the data. This study analyzed the operations and seek for improvements to its business processes through BPMN. The mapping of internal and external factors was completed to find the operational strategy. Furthermore, also business processes redesign was performed based on the strategies that have been formulated. Keywords: online, fashion, operational strategy, bpmn, swot